Outcomes of Conservative Management in a Clinically Stable Patient with Traumatic Liver Injury - Hassan Shahab, Omer Bin Khalid, Bushra Jawaid, Sumbla Salman, Unaiza Erum, Komal Faheem (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this research was to examine the success of non-surgical therapy for patients in stable condition who had come with serious liver injuries to the emergency department of a public tertiary care hospital in Karachi, Pakistan. Method: This retrospective research was carried out between February 2022 to August 2022 in department of General Surgery, Civil Hospital Ruth Pfau, DUHS, Karachi, after the ethical approval of the institute ethical review board. Patients were divided into two groups, group I receiving conservative care and group II undergoing surgery. Demographics, injury categorization, related lesions, surgical therapy, morbidity, mortality, and length of hospital stay were all were recorded through a questionnaire. Results: The average age of the 200 participants in the present research was 39.15± 10.47 years. There were 133 (66.5%) males who sustained injuries. The majority of patients (n=150, 75%) were found to have only mild liver damage (grades I–III), whereas 50 patients (25%) had more severe liver damage (grades IV–V). 150 patients (75%) were treated with conservative (NOM) care, whereas 50 patients (25%) had surgical intervention. Twenty-one deaths (10.5 %) were recorded in total. Conclusion: Conservative care is the preferred course of action for patients with stable hemodynamics, whereas surgical intervention is the treatment of choice for those with hemodynamic instability. Patients undergoing conservative treatment should be closely monitored. Mortality and morbidity rates were not significantly higher in patients whose conservative therapy failed.